Transcriptome analysis reveals defense responses of alfalfa seedling roots to Sclerotium rolfsii - Jia, Shizhen; Dan, Zhencuo; Li, He; Guo, Yuhan; Jia, Lei; Yu, Ailing; Zhan, Huitong; Liu, Xiangjun; Gao, Teng; Shi, Yun; Wang, Zeng-Yu; Cong, Lili (Frontiers in Plant Science, 2025)
IntroductionSclerotium rolfsii is a major pathogen responsible for root rot in various plants, including alfalfa (Medicago sativa). Additionally, this pathogen can also cause root diseases in alfalfa relatives, such as Medicago truncatula, soybean (Glycine max), and mung bean (Vigna radiata). This study aims to explore the interaction mechanisms between alfalfa and S. rolfsii, identify key regulatory factors involved in disease resistance, and provide insights for improving alfalfa's resistance to root rot. MethodsIn this study, the S. rolfsii strain CZL1 was isolated and identified as the primary pathogen responsible for root rot outbreaks in Qingdao, Shandong Province. M. sativa cv. WuDi was used as the experimental material. After inoculating the plants with strain CZL1, root samples were collected at 24 hours post-inoculation (hpi) and 4 days post-inoculation (dpi) for transcriptome sequencing.ResultsA total of 11,433 and 12,063 differentially expressed genes (DEGs) were identified at CK (Control, non-inoculated) versus T24 h (24 hpi) and CK versus T4 d (4 dpi), respectively. Plant hormone signal transduction pathways exhibited the highest number of DEGs at 24 hpi, while plant-pathogen interaction pathways were dominant at 4 dpi. Key genes in these pathways include PR-1 (Pathogenesis-Related protein 1), PPR (Pentatricopeptide Repeat protein), and F-box (F-box Kelch-repeat protein). Additionally, the phenylpropanoid biosynthesis pathway, which is involved in lignin and flavonoid synthesis, plays a crucial role in disease resistance. Important genes involved in this pathway, such as PAL, C4H, 4CL, CHS, and CHI, were found to be significantly enriched. Furthermore, the WRKY transcription factor family was identified as a key regulator of multiple metabolic pathways related to disease resistance.ConclusionThe findings provide a comprehensive understanding of the key molecular factors involved in alfalfa’s response to S. rolfsii infection, laying a theoretical foundation for future research on disease resistance mechanisms in alfalfa.